Sports Economics: Present and Future Impact on General Economics 2012
DOI: 10.1515/9783110511185-002
|View full text |Cite
|
Sign up to set email alerts
|

One for Sure or Maybe Three

Abstract: In order to avoid too many tied games after playing the five-minute overtime period, the National Hockey League (NHL) introduced two rule changes in the 1999-2000 season. First, a team that loses in overtime receives one point instead of zero points. Second, the number of skaters in overtime is reduced from five to four. The theoretical literature analyzing these rule changes predicted that they would also produce the unintended side-effect that more games would reach overtime and recommended that a team that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…A related control variable we also considered was whether or not the game was a divisional one. However, this game trait was previously found to be a nonsignificant predictor for the likelihood of overtime in PS3 (Franck & Theiler, 2012), and we feel that conference status may be the stronger predictor as far as team strategy. Specifically, while winning a division guarantees a top three playoff seed within a conference, the remaining five playoff teams can come from any division within that conference.…”
Section: Our Approachmentioning
confidence: 50%
See 3 more Smart Citations
“…A related control variable we also considered was whether or not the game was a divisional one. However, this game trait was previously found to be a nonsignificant predictor for the likelihood of overtime in PS3 (Franck & Theiler, 2012), and we feel that conference status may be the stronger predictor as far as team strategy. Specifically, while winning a division guarantees a top three playoff seed within a conference, the remaining five playoff teams can come from any division within that conference.…”
Section: Our Approachmentioning
confidence: 50%
“…The reward for overtime or shootout victories, meanwhile, was kept at two points. Franck and Theiler (2012) found that overtime likelihood in the Swiss NL did not change after the 2006 rule change. Perhaps the NHL, as it considers a…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, not only would it be difficult to ascertain information about which players chose to play abroad during this period, such an analysis could be compromised by the myriad changes to league policies made before the start of the 2005-2006 season, including the implementation of the shootout, which were designed to increase game scoring and excitement. Franck and Theiler (2012) and Lopez (2015), for example, identified changes in game outcomes when comparing behavior before and after the 2004 lockout. In this respect, the analysis of the 2012 lockout would be preferred; when NHL play resumed in January 2013, it did so with, by and large, an identical set of rules and incentives to the previous season.…”
Section: Discussionmentioning
confidence: 99%